2016
DOI: 10.1111/afe.12145
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of noctuid moths and damage forecasting in sugar beet

Abstract: 1 The most damaging Noctuidae pests in sugar beets in Croatia are classified into two groups based on the injuries that their larvae produce: the cutting species (Agrotis ipsilon and Agrotis segetum) and the surface-feeding species (Mamestra brassicae, Lacanobia oleracea and Autographa gamma). 2 The flight activity of male moths was detected and monitored using traps baited with sex pheromone. 3 The study aimed to determine the population dynamics of noctuid pests in sugar beet crops and to propose damage fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The turnip moth, Agrotis segetum Denis and Schiffermaller (Lepidoptera: Noctuidae), is a pest of wide geographic distribution and agricultural importance [ 29 , 30 , 31 ]. Previous research has shown that Chinese populations of A. segetum undertake seasonal migration [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…The turnip moth, Agrotis segetum Denis and Schiffermaller (Lepidoptera: Noctuidae), is a pest of wide geographic distribution and agricultural importance [ 29 , 30 , 31 ]. Previous research has shown that Chinese populations of A. segetum undertake seasonal migration [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…The population abundance and damages on sugar beet leaves are substantially impacted by air and soil temperature, as well as rainfall [7,[25][26][27]. Sugar beet seeds are treated with insecticides (often neonicotinoids) during seed processing and so, in the early stages of germination and emergence, crops are protected from pests for a short time [28]. Later in vegetation, sugar beets are increasingly attacked by a variety of pests as a result of favorable weather conditions.…”
Section: Moths On Sugar Beetsmentioning
confidence: 99%
“…However, the number of adult moths in pheromone traps is not always a direct indicator of the number of larvae, the life stage that damages the plants [33,34]. Lemic et al [28] established a strong positive correlation between captured male noctuid moths and the level of damage in sugar beet crop, and extreme relation of population density and weather conditions. However, for precise forecasting and decision about insecticide application in sugar beer field, visual inspections of moth damages are required [5,7].…”
Section: Moths On Sugar Beetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Predicting the impact of herbivore abundance on plants has a long history in crop pest forecasting (Magarey and Isard 2017), where it is used to support decision making regarding the scheduling of pest management interventions. For example, Lemic et al (2016) found a strong positive correlation between the number of noctuid moths caught in pheromone traps and damage to sugar beet crops, which can be used to inform the timing of insecticide application to keep damage under an economical threshold level. This principle is also used, among many others, in the management of codling moth in apple orchards (Rather et al 2018), of western corn rootworm in maize (Kos et al 2014) and of navel orangeworm in almond plantations (Rosenheim et al 2017).…”
Section: Introductionmentioning
confidence: 99%